Identification of male genotypes in Pistacia vera L. species using SSR markers - Alhajjar, Najwa Motaeb; Muzher, Bayan Mohammed (International Journal of Environment, 2017)
Genetic identification among different 15 male genotypes of Pistacia vera L. species in comparison with five main commercial male cultivars accredited by Ministry of Agriculture (Adam, Jamil, Ebrahim, Elyas and Khalifa) was achieved using SSR markers. Seventeen primer pairs out of Twenty SSR primers were able to amplify PCR products. SSR segregation produced 44 putative alleles, of which 34 were polymorphic (77.27%). Genetic similarity among all studied genotypes ranged from 0.45 between Jamil cultivar and MAS1 genotype to 1 between Ebrahim cultivar and MA1 genotype which means that they are identical. The UPGMA cluster analysis based on Jaccard’s coefficient grouped all genotypes into three main clusters. The number of alleles revealed by each SSR analysis ranged from 1 to 5, with a high level of expected heterozygosity (He) 0.507. Co-dominant SSRs loci were observed in some studied genotypes giving a value 0.235 of observed heterozygosity (Ho). According to the polymorphic allele’s number and the expected heterozygosity; Marker Index (MI) was 23.97. Our results concluded that SSR marker is an informative technique, which revealed high ability to differentiate individuals, and played an important role as a genetic marker for identification and evaluation studies within P. vera species.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-6, Issue-2, Mar-May 2017, Page: 30-42